2017
DOI: 10.7863/ultra.16.04064
|View full text |Cite
|
Sign up to set email alerts
|

Can Contrast‐Enhanced Sonography Detect Bowel Wall Fibrosis in Mixed Inflammatory and Fibrotic Crohn Disease Lesions in an Animal Model?

Abstract: Contrast-enhanced sonographic quantitative perfusion parameters failed to effectively detect bowel wall fibrosis in the setting of superimposed inflammation in a Crohn disease animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(45 reference statements)
2
4
0
Order By: Relevance
“…A study by Ripollés et al [20] demonstrated that inflammatory lesions had greater contrast enhancement when compared to fibrotic lesions. Additionally, our patient had a low elastography value, which was consistent with previous studies that demonstrate decreased tissue stiffness associated with acute inflammation when fibrosis is not present [192223]. Together, these findings suggest acute inflammation without the presence of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A study by Ripollés et al [20] demonstrated that inflammatory lesions had greater contrast enhancement when compared to fibrotic lesions. Additionally, our patient had a low elastography value, which was consistent with previous studies that demonstrate decreased tissue stiffness associated with acute inflammation when fibrosis is not present [192223]. Together, these findings suggest acute inflammation without the presence of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…They found that no quantitative parameter could reliably detect fibrosis [23]. Strictures often contain both inflammatory and fibrotic components, and as such, CEUS perfusion parameters are predominantly affected by the degree of inflammation [23]. Our results are consistent with this study, as CEUS effectively identified the presence of acute inflammation, but a lack of contrast enhancement was common to both the surgical fibrotic stricture and the chronic inflammation with stricture formation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…23 Similar observations were noted also in an animal model of CD. 24 This could be attributed to coexistence of mural fibrosis and active inflammation in varying amounts. Nevertheless, the results of a case series of three patients (two adolescents and one young adult) who underwent CEUS, shear wave elastography and MR enterography support the potential of CEUS to correctly discriminate between inflammatory and fibrotic strictures in CD.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently conducted animal study, imaging parameters derived from time-intensity curve analysis were compared to histopathological scores of tissue samples obtained from thickened bowel wall segments with experimentally induced inflammation mixed with variable degrees of fibrosis. In this study, quantitative CEUS perfusion parameters failed to differentiate bowel wall fibrosis if significant inflammation coexisted [ 57 ].…”
Section: Contrast-enhanced Ultrasound For Adults With Inflammatory Bowel Diseasementioning
confidence: 99%